La promoción del cumplimiento normativo: la visión del régimen sancionador administrativo de Ositran y Oefa - Morón Urbina, Juan Carlos (2025)
This article presents a comparative analysis of two models of state regulation: The traditional ‘command and control’ approach, focused on the imposition of sanctions, and the responsive approach, which advocates for a more flexible system based on cooperation, persuasion, and the use of incentives to promote regulatory compliance. Through this comparison, the authors reflect on which model may lead to a more effective and context-appropriate regulatory framework.In this context, the article examines the incentive regimes implemented by the Peruvian regulatory agencies OSITRAN and OEFA, assessing whether they align with the principles of responsive regulation. It analyzes how these mechanisms have been designed, the extent to which they have been implemented in practice, and the key challenges they face in becoming effective tools within the Peru’s regulatory system.